Perencanaan Strategis Sistem Informasi Bisnis Pada Lembaga Kursus Dan Pelatihan Rantau Rasau Link - Suryadi, Heri; Roestam, Rusdianto (Jurnal Manajemen Sistem Informasi, 2021)
Strategic planning of information systems is indispensable by an organization before developing an information system. This is done to minimize and prevent failures in information system investments that may cause the purpose of the information system to be out of line with the organization's objectives. To support the realization of the vision and mission of the Rasau Link Regional Course and Training Institute, the authors conducted research and drafted, and proposed an information system strategic planning framework based on the strategic planning methodology of information systems by Ward and Peppard supported by SWOT Analysis, Porter Value Chain, Key Factors of Success (CSF) and Application Portfolio. Based on the results of the analysis that has been done in this study can be known important factors necessary in the development and application of information systems, as well as the applications needed to manage the data and support the business functions of the main activities of the Course Institute and Training Rantau Rasau Link.